Pengetahuan, Sikap dan Praktik Peserta Didik Sekolah Menengah Pertama tentang Gizi Seimbang - Selvi Selvi; Marsela Dervina Amisi; Yulianty Sanggelorang (Universitas Sam Ratulangi, 2021)
Background: Balanced nutrition is a daily diet that contains nutrients in the type and amount according to the body’s needs while still paying attention to the principles of consuming a variety of foods, having a clean and healthy lifestyle, doing physical activity and weighing body weight regularly.The level of knowledge and attitude of a person’s balanced nutrition affect his practice in implementing balanced nutrition. The objective of this research is to analyze the balanced nutritional behavior of students at SMPN 6 Sa'dan, North Toraja Regency. Methode: The research methods used an analytical survey research design with cross sectional. the population of this research is 156 students. The sample used of 154 students. Data analysis is using the spearman correlation test. Result: The results in the research show that students have a sufficient level of knowledge (46,8%), the attitudes about balanced nutrition is generally good (82,5%) and balanced nutrition practices is generally good (68,8%). Based on the results shows there is not relationship between knowledge of balanced nutrition and balanced nutrition practices, with p value = 0,634 and r value = 0,040. There is a relationship between balanced nutrition attitudes and balanced nutrition practices of students in the SMPN 6 Sa’dan, North Toraja Regency, with p value = 0,000 and has a moderate relationship indicated by correlation value of r = 0,407 and show a positive direction. Conclusion: the conclusion show there is not relationship between knowledge of balanced nutrition and balanced nutrition practices and There is a relationship between balanced nutrition attitudes and balanced nutrition practices of respondents